2014
DOI: 10.1177/0891988714522701
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Montreal Cognitive Assessment and Discriminant Power of Montreal Cognitive Assessment Subtests in Patients With Mild Cognitive Impairment and Alzheimer Dementia in Turkish Population

Abstract: Montreal Cognitive Assessment (MoCA) is a new cognitive tool developed for screening mild cognitive impairment (MCI). The authors examined validity of MoCA and discriminating power of subtests in a Turkish population comprising of 474 participants (246 healthy controls, 114 subjects with MCI and 114 subjects with dementia). The ANCOVAs showed that age and education had a main effect on MoCA scores. Cut scores were computed according to different education levels. The overall cut-off values for MCI and dementia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 30 publications
6
48
1
4
Order By: Relevance
“…Studies have demonstrated that the culturally and linguistically adapted versions of the MoCA are superior to the MMSE in screening for MCI [20,28,29], however, due to the differences in Western culture and difficulty in separating the influence of culture from education level, further revision of MoCA adaptations are required to tailor the contents more accurately to local populations across the globe as well as optimizing cut-offs for detecting MCI.…”
Section: Cross Cultural Cognitive Assessmentmentioning
confidence: 99%
“…Studies have demonstrated that the culturally and linguistically adapted versions of the MoCA are superior to the MMSE in screening for MCI [20,28,29], however, due to the differences in Western culture and difficulty in separating the influence of culture from education level, further revision of MoCA adaptations are required to tailor the contents more accurately to local populations across the globe as well as optimizing cut-offs for detecting MCI.…”
Section: Cross Cultural Cognitive Assessmentmentioning
confidence: 99%
“…Чувствительность и специфичность MMSE и МоСА в разных возрастных группах вариабельны и зависят от нейропсихологического профиля и уровня образования [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Кроме того, большин-ство шкал адаптировано к амбулаторной оценке и их использование в условиях стационара может быть затруднено.…”
Section: Discussionunclassified
“…Порог отсечения, который обсуждается для шкалы МоСА, вариабелен, однако большинство авторов указывают на значение 24-26 баллов [14][15][16][17][18][19]. В нашей работе максимальную чувствитель-ность и специфичность (65,0 и 77,8% соответствен-но) удалось получить при крайне низком пороге отсечения в 19 баллов.…”
Section: Discussionunclassified
“…These results correspond in part to those of Kaya et al (2014), who compared MoCA scores for 114 patients with mild cognitive impairment and 246 healthy controls. The authors reported that the most useful domains in discriminating mild cognitive impairment from normal cognition were recall, visuospatial, and language.…”
Section: Validitymentioning
confidence: 77%
“…It is also well known that education has a main effect on cognitive assessment scores, while sex does not (Kaya et al, 2014). We suggest correcting the ZüMAX for education In our study, the control group was much more educated than the patients (Table 1).…”
Section: Validitymentioning
confidence: 91%